Radical Transparency Membangun Kepemimpinan SDM dengan Sistem Gaji Terbuka (Salary Transparency): (Fokus Dampak Psikologis dan Manajerial dari Keterbukaan Informasi Financial di Organisasi) (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
Transparency in human resource management has become a strategic issue in modern organizations, particularly through the implementation of salary transparency as part of the broader concept of radical transparency. This study aims to analyze the psychological and managerial impacts of salary information disclosure and its implications for human resource leadership within organizations. The research employs a qualitative approach using a narrative literature review by examining relevant scholarly articles published within the last five years. The findings indicate that salary transparency contributes positively to enhancing employees’ perceptions of fairness and trust; however, it may also generate negative consequences such as social comparison, interpersonal conflict, and decreased job satisfaction if not properly managed. From a managerial perspective, salary transparency promotes greater accountability, strengthens performance evaluation systems, and encourages more open and participative leadership practices. This study contributes by integrating psychological and managerial dimensions into a comprehensive conceptual framework and highlights the importance of organizational readiness in strategically managing transparency policies to achieve effectiveness and sustainability.